The Effect of Exercise on Postpartum Women’s Quality of Life: A Systematic Review - Ni Putu Dian Ayu Anggraeni; Lucky Herawati; Melyana Nurul Widyawati; I Komang Leo Triandana Arizona (Universitas Airlangga, 2019)
Postpartum mothers are vulnerable to several problems during the puerperium, such as fatigue, sleep disorders, anxiety, depression, sexual problems, physical functioning and dissatisfaction with partner support that can affect their quality of life. The aim of this systematic review is to explore the effect of exercise on postpartum women’s quality of life. Comprehensive searches including experimental studies (including RCTs and non-randomized trials) from several databases, namely Scopus, PubMed, and Science-Direct, were used to search for scientific contributions published between 2009 and 2019. The articles are identified using the relevant keywords. This systematic review is guided by PRISMA. Fourteen of the 636 articles met both the inclusion and exclusion criteria. The postpartum exercises found in this study were Yoga, Pelvic Floor Muscle Training (PFMT), Pilates, Postnatal Exercise, Aerobic Exercise and Progressive Muscle Relaxation (PMR). This review cannot provide definitive conclusions about the best form of exercise, the suggested duration or the timing needed to improve the quality of life for postpartum women. However, Yoga and Pilates are proven to effectively improve maternal well-being because this exercise focuses on increasing the physical, psychological and social support during the postpartum period. Further research is needed to provide evidence and to strengthen the results of this systematic review.